The genus Astrocaryum (Arecaceae) - Kahn, Francis (2008)
The palm genus Astrocaryum with 40 species is common in tropical South America extending northwards reaching Central America and Trinidad. Twenty-six species grow in Brazil, 14 in Peru, 11 in Colombia, 9 in Guyana, 9 in Suriname, 8 in Bolivia, 8 in French Guiana, 6 in Venezuela, 4 in Ecuador, 2 in Costa Rica, 2 in Panama, and 1 in Trinidad. The genus includes solitary or caespitose species in the following classes: (i) large palms with tall stem, (ii) palms with large leaves and medium-sized, or short, or subterranean stem, (iii) slender to mediumsized palms, (iv) acaulescent palms with very short leaves. Although most Astrocaryum species are used by humans, only a few may have promising economic potential and are significantly important in the local and regional trade. In this article, I propose a new taxonomic classification based on characters of the fruit, flowers and vegetative parts. The genus is divided in three subgenera: (i) Munbaca with two sections, Munbaca and Mumbacusu, each with 2 species; (ii) Astrocaryum with two sections, Euchambira (new section with 1 species) and Astrocaryum with three subsections — Astrocaryum (9 species), Acaulia (5 species) and Perstaminata (new subsection with 1 species); (iii) Monogynanthus with four sections: Monogynanthus (with 3 species), Ayri (1 species), Guatinajo (new section with 1 species) and Huicungo (new section) that includes three subsections — Huicungo (7 species); Sachacungo (new subsection with 5 species), and Murumuru (3 species). A synoptic review of the genus is presented herein, including descriptions and illustrations as well as data on distribution, habit, ecology and common names for each species. An identification key to all species is also supplied.